Degree of sustainability reporting in Singapore : a prescriptive model for companies. - Nguyen, Quynh Phuong. (2012)
This paper identifies potential factors that contribute to the differences in the degree of sustainability reporting in Singapore listed companies. Annual reports of 563 eligible companies listed on the SGX Main Board in the period 2008-2010 were collected and assigned with scores according to their sustainability disclosure level, graded through the Global Reporting Initiative framework. Relationships between the independent variables namely Firm Size (represented by Revenue), Firm Leverage (measured by Debt-to-Equity Ratio) and Firm Profitability (quantified by Return on Assets) and the dependent variable, the Degree of Sustainability Reporting, respectively were then studied and tested. The performance of companies belonging to different industries and the performance of the same company within three different reporting years was also compared. Results showed that the correlations between Firm Size and Firm Leverage to the Degree of Sustainability Reporting respectively are statistically significant while there is no clear relationship between Firm Profitability and Industry Membership to the Degree of Sustainability Reporting. Across different years, companies’ Sustainability Reporting scores were also found to have improved, though not by a large degree. An equation was formulated from a multiple regression of the various factors, which can subsequently be used by firms to calculate the expected level of disclosure they should make, given their current characteristics. The equation is a simple and intuitive measure for which firms could easily assess their sustainability reporting standing relative to their peers listed on the SGX.